A Model of Waste Management Improvement In Indonesia - Yefta. A. K. Noegroho, Suzy Noviyanti, Jony. O. Haryanto, Lanita Winata (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
Waste management (garbage) is an important thing and cannot be negotiated by any companies.Â By applying a good waste management system, companies will be the companies that are pro-environment and they will be positively appreciated by their stakeholders.Â This study aims to examined the factors that influence the waste management and their impacts on the financial performance of the company through a model to determine the antecedents of commitment and waste management program that eventually lead to improve financial performance.Â This research was conducted by distributing questionnaires to 100 managers of companies that implement waste management programs.Â The results showed that there was a positive influence of awareness and legal compliance towards its environmental commitments and positive influence on the environmental commitment program of waste management and waste management programs towards the financial performance of the company.Â The waste management program could make the companies prepare their operation better and minimize their environment cost. This study also gives a boost to companies that wants to improve the company's financial performance through waste management program.